Exploring anxiety and sleep disorders among Edna Adan university students in Somaliland: associated stressors and insights - Peiter Gideon; Alemayehu Bayray (BMC Psychology)
Abstract Background 970 million people around the world are living with mental illness. Mental illness is also one of the chronic diseases prevalent in Somaliland. Anxiety and sleep disturbances are the major types of mental illness commonly observed in young adults. The purpose of this study is to explore the anxiety, sleep disturbances, and their factor associated with Edna Adan University bachelor’s students in Hargeisa, Somaliland. Methods This study has used a cross-sectional study with 307 bachelor students of Edna Adan University as its participants from May to July 2024. GAD-7 was used to evaluate anxiety; MPAI was used to measure mobile phone addiction; and GSDS was used to measure sleep disturbances. Pre-test for associated factors questionnaire was carried to assess the validity and reliability of questionnaire. The acquired data was then univariate and analyzed in SPSS version 26. Results Most 71.30% of the students reported having a good sleep quality, 63.50% had no problem with mobile phone addiction, and 61.20% experienced minimal to no anxiety. Academic stressors, financial pressure, and interpersonal relationships are the most frequently (9.10%) experienced linked factors with a very serious frequency (all of the time), followed by several other factors, such as teaching and learning-related stressors, mental illness and use of psychoactive substances, language barrier, body mass index (BMI) or daily meal problem, having doubt regarding the future or gambling behavior, and travel time to university. Conclusion This study shows that the students mainly have minimal to no anxiety, and no addiction to mobile phone while maintaining a good sleep quality. However, sleep disturbances and anxiety-associated factors such as academic stressors, financial pressure, and interpersonal relationships are commonly experienced in a very serious frequency (all of the time).